Habitus Pengembangan Desa Wisata Kampung Topeng Pada Warga Binaan Kelurahan Tlogowaru Kecamatan Kedung Kandang - Dini, Alya Muflihatud; Ardiansyah, Adistya Eka Sis; Harahap, Adinda Putri; Huda, Ahmad Tirtho Faidl; Azzahra, Annisa Shafa (Asketik: Jurnal Agama dan Perubahan Sosial, 2022)
The involvement of residents in the development of tourist villages is a very appropriate form of formulation in the sustainable development of tourist villages. This study aims to determine the habits of the fostered residents in the development of the tourist village of Kampung Mask, Tlogowaru Village, Kedungkandang District, by looking at the social practices that take place in it. The theory used is Pierre F Bourdieu's theory of social practice. The research uses qualitative methods with data collection techniques through participatory observation, open interviews, documentation, and relevant literature studies. Interviews were conducted on research subjects who were selected through a purposive sampling technique in which the informants consisted of the management of the village of mask tourism, namely the head of the welfare institution for the Prosperous People, the assisted residents who live there and related stakeholders/elements. The data collection instrument uses interview sheets, observation sheets, documentation tools and other tools needed in the data collection process. To ensure data validity, the researcher applies data source triangulation and data analysis techniques, namely Miles & Huberman interactive analysis. The study results indicate that the habitus and capital owned by the assisted residents in the village of mask tourism have yet to be utilized and developed optimally. The lack of attention to the habitus and capital of the inmates, which, by optimizing the habitus and capital, can contribute to the development of the Kampung Mask tourist village. In addition, it can be seen that there is no maximum utilization of natural potential due to limited economic capital and the inmates' mindset that has not changed.